The levels of RAC3 expression are up regulated by TNF in the inflammatory response - Cecilia Viviana Alvarado (FEBS Open Bio, 2014)
RAC3 is a coactivator of glucocorticoid receptor and nuclear factor-κB (NF-κB) that is usually over-expressed in tumors and which also has important functions in the immune system. We investigated the role of the inflammatory response in the control of RAC3 expression levels in vivo and in vitro. We found that inflammation regulates RAC3 levels. In mice, sub-lethal doses of lipopolysaccharide induce the increase of RAC3 in spleen and the administration of the synthetic anti-inflammatory glucocorticoid dexamethasone has a similar effect. However, the simultaneous treatment with both stimuli is mutually antagonistic. In vitro stimulation of the HEK293 cell line with tumor necrosis factor (TNF), one of the cytokines induced by lipopolysaccharide, also increases the levels of RAC3 mRNA and protein, which correlates with an enhanced transcription dependent on the RAC3 gene promoter. We found that binding of the transcription factor NF-κB to the RAC3 gene promoter could be responsible for these effects. Our results suggest that increase of RAC3 during the inflammatory response could be a molecular mechanism involved in the control of sensitivity to both pro- and anti-inflammatory stimuli in order to maintain the normal healthy course of the immune response.